Bootstrap Variance Estimation of Nonlinear Functions of Parameters: An Application to Long-Run Elasticities of Energy Demand - Li, Hongyi; Maddala, G. S. (The Review of Economics and Statistics, 1999)
In many practical applications, one is interested in obtaining confidence intervals for nonlinear functions of the parameters. This paper considers the following different methods: Fieller's method, Taylor's series expansion, and bootstrap methods. Compared to some of the earlier results in the empirical studies that are against the application of bootstrap, our results suggest a different conclusion in favor of the bootstrap methods.